2008
DOI: 10.1103/physreve.78.040101
|View full text |Cite
|
Sign up to set email alerts
|

Exhaustive enumeration unveils clustering and freezing in the random 3-satisfiability problem

Abstract: We study geometrical properties of the complete set of solutions of the random 3-satisfiability problem. We show that even for moderate system sizes the number of clusters corresponds surprisingly well with the theoretic asymptotic prediction. We locate the freezing transition in the space of solutions which has been conjectured to be relevant in explaining the onset of computational hardness in random constraint satisfaction problems. PACS numbers: 89.20.Ff,75.10.Nr,89.70.Eg Satisfiability (SAT) is one of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
43
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(47 citation statements)
references
References 30 publications
(101 reference statements)
3
43
1
Order By: Relevance
“…In fact, non-rigorous arguments as well as experimental evidence [5] suggest that the picture is quite different and rather more complicated for "small" k (say, k = 3, 4, 5). In this case the various phenomena that occur at (or very near) the point 2 k ln(k)/k for k ≥ 10 appear to happen at vastly different points in the satisfiable regime.…”
Section: A Digression: Replica Symmetry Breakingmentioning
confidence: 99%
“…In fact, non-rigorous arguments as well as experimental evidence [5] suggest that the picture is quite different and rather more complicated for "small" k (say, k = 3, 4, 5). In this case the various phenomena that occur at (or very near) the point 2 k ln(k)/k for k ≥ 10 appear to happen at vastly different points in the satisfiable regime.…”
Section: A Digression: Replica Symmetry Breakingmentioning
confidence: 99%
“…Later at the condensation transition point α = α c the solution space becomes dominated by only a few Gibbs states (for the special case of K = 3, the clustering and the condensation transition coincide). It was also found that some variables will become frozen to the same spin value in all the solutions of a Gibbs state [31,32], this fact has serious consequences for stochastic local search algorithms.…”
Section: The Random K-satisfiability Problemmentioning
confidence: 99%
“…Our simulation results reveal that the jamming constraint densities α j as obtained for many trajectories of SEQSAT on the same random K-SAT formula and on different random K-SAT formulas are very close to each other. It is anticipated that, in the thermodynamic limit of N → ∞, the SEQSAT process has a true jamming transition at a critical constraint density α located at α = α f = 4.254 [32], while that for the random 4-SAT problem is located at α f = 9.88 [31]. These threshold constraint densities correspond to the appearance of frozen variables in the dominating Gibbs states of the solution space.…”
Section: Long-range Frustration Theory On the Jamming Transitionmentioning
confidence: 99%
“…In a phase with a large number of small clusters we will miss small clusters if they only comprise a negligible part of the solutions (in the sense of the stopping criterion) and therefore underestimate the number of clusters. It is therefore natural that the complexity found here is lower than the one given in [26]. After all the complexity shown in the graph is only a lower bound for the true complexity respecting all clusters.…”
Section: B Averaged Quantitiesmentioning
confidence: 67%
“…Therefore in [26] a different notion of frozen clusters via the whitening core is used. There one looks, for each solution, interatively for variables which can be flipped since they appear only in clauses satisfied by other variables or which contain variables already detected in the whitening core.…”
Section: B Cluster Phenomenamentioning
confidence: 99%